Digital filter design for ECG body signal - Wang, Xin. (2010)
The ECG (electrocardiogram) is a time-varying signal which represents the successive atrial and ventricular depolarization/ repolarization which occurs with every heart beat. The noise elimination for ECG signal is considered as a classical problem. A digital FIR low pass filter is proposed for the removal of relative high frequency noise. It will be implemented to FPGA for design verification.